Propuesta de adaptación del reglamento de fútgolf para personas con parálisis cerebral (2021)
The adapted Footgolf is not among the sports modalities of the Spanish Sports Federation for People with Cerebral Palsy and Acquired Brain Damage. Therefore, the objective of the present work is to carry out a proposal to adapt the Footgolf regulations for people with cerebral palsy based on the functional classification of soccer player. Taking the conventional Footgolf regulation as a reference, an adaptation of materials, sports facilities, and technical-tactical aspects has been carried out. The practice of sport by people with disabilities in general and with cerebral palsy, in particular, can have different benefits in physical condition, as well as at a psychological, physical, social, work, functional and recreational level, that improve the quality of life and facilitate the inclusion of this population.